Updating the Comparative Evidence on Second‐Generation Antipsychotic Use With Schizophrenia. Issue 2 (16th October 2020) - McDonagh, Marian S.; Dana, Tracy; Selph, Shelley; Devine, Emily B.; Cantor, Amy; Bougatsos, Christina; Blazina, Ian; Grusing, Sara; Fu, Rongwei; Haupt, Daniel W.
Abstract: Objective: The objective of this study was to conduct a systematic review of literature comparing second‐generation antipsychotics (SGAs) with each other and with first‐generation antipsychotics (FGAs) in treating schizophrenia. Methods: MEDLINE, the Cochrane Library, and PsycINFO databases were searched through January 2020. Following standard methods, recent high‐quality systematic reviews of each drug comparison and subsequently published primary studies were included to update the meta‐analyses with any new data. Two reviewers independently conducted study selection, abstraction, and quality assessment. Results: Two systematic reviews and 29 newer trials (total of 162 trials of SGAs, N=53, 861; 116 trials of SGAs versus FGAs, N=119, 558) were included. Most trials were of fair quality, industry‐funded, and included older SGAs and a few recently approved SGAs (asenapine, lurasidone, iloperidone, cariprazine, brexpiprazole and long‐acting injection [LAI] formulations of aripiprazole and paliperidone). Older SGAs had similar effects on function, quality of life, mortality, and adverse event incidence, although clozapine improved symptoms more than most other drugs and olanzapine and risperidone were superior to some other drugs. Olanzapine, risperidone, ziprasidone, and aripiprazole performed similarly on outcomes of benefit compared with haloperidol. Risperidone LAI and olanzapine resulted in fewer withdrawals due to adverse events, but risk of diabetes increased with olanzapine. Haloperidol had greater incidence of adverse events than did olanzapine and risperidone, but similar effects on other outcomes. Conclusions: Most comparative evidence favored older SGAs, with clozapine, olanzapine, and risperidone superior on more outcomes than other SGAs. Older SGAs had similar benefits as haloperidol but with fewer adverse events. HIGHLIGHTS: Use of the second‐generation antipsychotics olanzapine, aripiprazole, risperidone, quetiapine, and ziprasidone resulted in similar function, quality of life, mortality, and overall incidence of adverse events. Core illness symptoms improved more with olanzapine and risperidone than asenapine, quetiapine, or ziprasidone, and more with paliperidone than lurasidone or iloperidone. Haloperidol showed similar benefits but more adverse events than did olanzapine or risperidone.